Urgensi Manajemen Sumber Daya Manusia (MSDM) Dalam Mengimplementasikan Wakaf Produktif (Studi Kasus Di BMT Al-Rifa’ie 2 Malang) - Nita Rahayu; Muhammad Ridwan Basalamah; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study is to analyze the human resource management system in the implementation of cash waqf starting from planning, organizing, implementing, and controlling at BMT Al-Rifa'ie Malang.The research method used is a qualitative approach. The type of research used is a case study. Researchers conducted observations, interviews, and other required data collection. Then the researchers collected data, processed the data to draw conclusions from the results of their research. The results of this study indicate that the role of a nadzir is very important to manage waqf institutions to be good, the risk of corruption is minimal, and not out of line with syar’i. Keywords: Management, Human Resource management, cash waqf